1991
DOI: 10.2527/1991.6931205x
|View full text |Cite
|
Sign up to set email alerts
|

Role of sulfur and chloride in the dietary cation-anion balance equation for lactating dairy cattle.

Abstract: Ten Holstein cows averaging 120 d in lactation were arranged in replicated 5 x 5 Latin squares with 3-wk periods to evaluate the role of sulfur (S) in the dietary cation-anion balance equation. Diets were based on corn silage in Exp. 1 and sorghum silage in Exp. 2. Supplemental S and chloride (Cl) from the double sulfate of potassium and magnesium and CaCl2 were used to manipulate dietary cation-anion balance from 0 to +30 meq when expressed as meq [(Na + K)-(Cl + S)]/100 g diet DM and from +19 to +49 meq when… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

14
46
1
7

Year Published

1994
1994
2016
2016

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 95 publications
(68 citation statements)
references
References 8 publications
14
46
1
7
Order By: Relevance
“…Similarly, Tucker et al (1992) observed that cows fed anionic diets in prepartum had higher blood concentration of iCa than cows fed cationic diets. Similar results were also reported by Tucker et al (1991) and Wu et al (2008). The increase of blood concentration of Ca can be a metabolic response to pH reduction of cellular and transcellular fluids, which stimulates the production of hormones PTH and 1.25 (OH 2 )D 3 , and depresses the action of calcitonin.…”
Section: Blood Metabolismsupporting
confidence: 86%
See 1 more Smart Citation
“…Similarly, Tucker et al (1992) observed that cows fed anionic diets in prepartum had higher blood concentration of iCa than cows fed cationic diets. Similar results were also reported by Tucker et al (1991) and Wu et al (2008). The increase of blood concentration of Ca can be a metabolic response to pH reduction of cellular and transcellular fluids, which stimulates the production of hormones PTH and 1.25 (OH 2 )D 3 , and depresses the action of calcitonin.…”
Section: Blood Metabolismsupporting
confidence: 86%
“…The table with ingredients proportion and chemical composition of experimental diets was described in detail in a companion paper (Martins et al, 2015). The DCAD levels were calculated based on Tucker et al (1991) using the formula: mEq/kg of DM = [(% Na in DM/0.023)…”
Section: Methodsmentioning
confidence: 99%
“…Similarly, Tucker et al (1988b) also reported a linear increase in plasma Cl -concentration with decrease in the DCAD levels (+20 to -10 meq/kg of DM). Increased plasma Cl -concentration in low DCAD fed cows might be due to high intake of CaCl 2, used for reduction of dietary DCAD level as reported by Tucker et al (1991). The plasma Na, K and Cl level in present finding is closely associated with increased blood pH in cows fed on high DCAD diet.…”
Section: A Linear Increase In Plasma CLsupporting
confidence: 75%
“…The feed mineral composition was determined (AOAC, 1995). DCAD was calculated using the formula of Tucker et al (1991) (meqK+meqNa)-(meqCl+meqS). Milk composition was determined on Milkoscan equipment, the levels of Ca, P inorganic and Mg in blood serum were determined photometricaly with the use of kits (POCH, Gliwice).…”
Section: Methodsmentioning
confidence: 99%